Comparison of Stock Portfolio Performance of Conventional Banks and Islamic Banks Using Sharpe Ratio, Treynor Ratio, and Jensen Ratio (2021-2023) - Abidah, Asiska Nur; Pratiwi, Putri Hidayanti; Oftafiana, Triya; Aswad, Muhammad (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
Before purchasing shares on the stock exchange, potential investors and investors need to measure the performance of the stock portfolio of companies listed on the stock exchange to identify the level of return to be received and whether the level of return is comparable to the risk borne to maximize the return. Along with the development of the Islamic sector in Indonesia, the stock exchange is filled with conventional stocks and Islamic stocks owned by companies that operate based on Islamic principles. Some researchers have different opinions regarding which stock performance is superior between Islamic and conventional stocks. This study aims to measure the performance of stock portfolios in Islamic banking and conventional banking and then compare the performance of both. This study used samples of conventional commercial banks such as BPTN Bank, Bukopin Bank, and CIMB Niaga Bank. At the same time, Islamic Commercial Banks were BPTN Syariah Bank, Panin Dubai Syariah Bank, and Bank Syariah Indonesia. The research methods used to measure stock portfolio performance are the Sharpe Method, Treynor Method, and Jensen Method. The study results show that the performance of the stock portfolio in conventional commercial banks using the Sharpe index, Treynor index, and Jensen index for 2021 to 2023 is superior to that of Islamic commercial banks.